Celebrating 200 Years of Humboldt University - Litta, Sebastian (International Higher Education, 2010)
The Universität zu Berlin, later renamed Humboldt Universität, was founded in 1810, and revolutionized the concept of a university to research institutions. While Humboldt is today in urgent need of reform, this university also forms the key part of the history of German higher education over the past 200 years. Humboldt University used to be the most successful university system in the world, which became a sclerotic and bureaucratic behemoth and only recently started to renew itself.